Seismic performance of a controlled rocking reinforced concrete frame. Issue 1 (January 2017) - Lu, Liang; Liu, Xia; Chen, Junjie; Lu, Xilin
A controlled rocking reinforced concrete frame is a new type of vibration control structure system that uses resilient rocking columns and joints. The effects of earthquakes on this type of structure are reduced by weakening the overall stiffness, whereas the lateral displacement is controlled by the energy-dissipation dampers introduced into the structure. Two tests were performed for research: the reversed cyclic loading test and shaking table test. Two single-span single-story controlled rocking reinforced concrete frames were designed for reversed cyclic loading tests. These tests (i.e. a column-base joint stiffness test, beam-column joint stiffness test, and frame stiffness test) were performed under different conditions. The mechanical analysis model of the rocking joints was derived from the test results. With the parameters obtained from the cyclic tests, a numerical simulation method that established the analytical model of the controlled rocking reinforced concrete frame using the program ABAQUS is proposed, and the dynamic time-history analysis results of the controlled rocking reinforced concrete frame and of the conventional approach are compared to investigate the vibration control effect and seismic performance of the controlled rocking reinforced concrete frame. In addition, the inter-story drift could be effectively controlled by adding metallic dampers, and the shaking table test models of the controlled rocking reinforced concrete frame with metallic dampers were designed and constructed. The comparison of the results of the numerical analysis and the shaking table test demonstrates that the model building of the controlled rocking reinforced concrete frame structure is efficient and that the controlled rocking reinforced concrete frame exhibits an excellent seismic performance.